Job burnout among Polish dentists: the role of sensory processing sensitivity and emotional intelligence - Beata Pszczółkowska; Sylwiusz Retowski (International Journal of Occupational Medicine and Environmental Health)
Objectives Job strain in dentistry makes the profession highly susceptible to occupational burnout. People with high sensory processing sensitivity (SPS) perceive workplace as more stressful and more demanding. Emotional intelligence (EI) is both a trait and an ability, which helps individuals adapt to the environment and reduces burnout. This study examines the relationship between SPS and burnout among Polish dentists and whether EI may be a protective factor against burnout in a group of highly sensitive dentists.